Penerapan Konsep Biokimia untuk Meningkatkan Pemahaman Materi Metabolisme pada Pembelajaran Biologi - Lutfiyah Nayla Hadeliyah; Miftahul Khairani; Rizky Melanie; Windry Yudansyahputi; Esy Alifa Nurwanty (CV. Rumoh Aceh Publishing, 2026)
Metabolism in biology learning is one of the complex concepts because it involves various biochemical processes occurring in living cells. Students often have difficulty understanding this topic because it is abstract and contains many reaction stages that must be learned in sequence. This study aims to examine the application of biochemical concepts in biology learning to improve students understanding of metabolism. The method used is a literature review by analyzing relevant scientific sources. The results show that the application of biochemical concepts can help students understand metabolic processes more clearly by linking chemical reactions with biological functions at the molecular level. In addition, the use of visual and technology based learning media also supports better student understanding. In conclusion, the integration of biochemical concepts in biology learning is effective in improving students understanding of metabolism.